Studi Hadis Tentang Wudhu Setelah Makan Makanan Olahan - Sri Sabilillah; Ilham Mustafa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The background of the problem in this research is the quality and understanding of the hadith about performing ablution after consuming processed food. The aim of this research is to determine the quality and understanding of the hadith. This is a qualitative research conducted through library research method, using the takhrij hadith approach with contextual approach. The hadiths are then evaluated to determine their quality. The understanding of these hadiths is then extracted from various books of Hadith commentary. Furthermore, the hadiths are interpreted using a contextual approach by understanding the context, situation, and purpose of the Prophet's hadith. The result of this research is that the hadith about performing ablution after consuming processed food is considered authentic (sahih) in terms of quality, but there are differences in its sources, some are marfu' (directly attributed to the Prophet) and some are mauquf (attributed to a companion). In understanding the hadith about performing ablution after consuming processed food, according to the scholars of Salaf, eating something that has been touched by fire does not nullify ablution, while another group believes that it is obligatory to perform ablution according to sharia because of touching something that has been touched by fire. The hadith that explains this command is to be understood as a sunnah (recommended) and not as an obligation.